Fabrication and failure mechanisms of all-composite honeycomb sandwich cylinder under the axial compression. (October 2022) - Li, Zhibin; Gao, Ying; Xue, Pengcheng; Wei, Xingyu; Du, Yuntong; Wang, Yan; Xiong, Jian
Graphical abstract: Highlights: Winding-based method is proposed to fabricate all-composite honeycomb sandwich cylinder (CHSC). The critical force of intracell buckling for exact hexagonal boundaries is derived based on the energy principle. Three-dimensional failure maps are derived to reveal multi-failure mechanisms of fabricated CHSC. Finite element analysis and experiments are conducted to explore the failure mode and verify the theoretical predictions. The CHSC has higher bearing capacity than other types of cylinders. Abstract: Winding-based method, an innovative technology, is proposed to successfully fabricate the all-composite honeycomb sandwich cylinder (CHSC). Excellent mechanical properties of CHSC can be achieved owning to continuous prepreg winding. The critical force of intracell buckling for exact hexagonal boundaries is proposed based on the energy principle, which has small difference between the simulation and experimental results. Three-dimensional failure maps are derived to reveal failure mechanisms of fabricated CHSC. Multi-failure mechanisms of CHSC under axial compression are explored by failure mechanism maps, which can more intuitively express the influence of dimensionless geometric parameters on failure modes. Failure modes of intracell buckling and face crushing were obtained by typical experiments under axial compression. The honeycomb sandwich cylinder prepared in this paper shows excellent bearing capacity compared to other types of sandwich cylinders. Winding-based method is expected to provide an important support for the fabrication of curved multifunctional honeycomb.